Peristaltic Transport through Eccentric Cylinders: Mathematical Model - Kh. S. Mekheimer; Y. Abd elmaboud; A. I. Abdellateef (Applied Bionics and Biomechanics)
This paper discusses the effect of peristaltic transport on the fluid flow in the gap between two eccentric tubes (eccentric-annulus flows). The inner tube is uniform, rigid, while the outer tube has a sinusoidal wave traveling down its wall. The flow analysis has been developed for low Reynolds number and long wave length approximation. The velocity and the pressure gradient have been obtained in terms of the dimensionless flow rate Q¯, time t, azimuthal coordinate θ and eccentricity parameter ϵ (the parameter that controls of the eccentricity of the inner tube position). The results show that there is a significant deference between eccentric and concentric annulus flows.